Obtaining Optimum Peel Color of Fresh Florida Citrus - Ritenour, Mark A.; Alferez, Fernando (EDIS, 2020)
This article informs about pre- and postharvest factors influencing citrus fruit peel color for fresh markets and the best postharvest treatment methods for obtaining excellent peel color. Peer reviewed through UF/IFAS Citrus Research and Education Center; published in Citrus Industry Magazine.